School teenagers, sexuality and the use of Paulo Freire's culture of culture (Revista Contexto & Educação, 2023)
The study aimed to identify the adolescents' practices and manifestations of their sexuality, through the use of the Culture Circle. This is an intervention research, developed with 15 adolescents from a state high school in Forquilha - Ceará, Brazil, in which educational actions were carried out following the steps proposed in the Paulo Freire Culture Circle. The search to know the aspects related to the adolescents' sexuality provided an exercise of self-knowledge and self-concept for the participants, revealing aspects of their daily lives such as generational conflicts and manifestations of sexuality in a contemporary perspective. The use of the Culture Circle instigated the protagonism, since the adolescents discussed controversial and relevant topics and even mediated knowledge among their peers.